2023
DOI: 10.1007/s11060-023-04308-4
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Treating Fields (TTFields) increase the effectiveness of temozolomide and lomustine in glioblastoma cell lines

Abstract: Purpose Tumor Treating Fields (TTFields) are electric fields that disrupt cellular processes critical for cancer cell viability and tumor progression, ultimately leading to cell death. TTFields therapy is approved for treatment of newly-diagnosed glioblastoma (GBM) concurrent with maintenance temozolomide (TMZ). Recently, the benefit of TMZ in combination with lomustine (CCNU) was demonstrated in patients with O6-methylguanine DNA methyltransferase (MGMT) promoter methylation. The addition of adj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…Patients with MGMT-methylated tumors had superior prognoses, potentially attributable to increased temozolomide (TMZ) sensitivity in these tumors ( 34 ). Notably, recent research on human GBM cell lines indicated a synergistic effect of combining TTFields with chemotherapy agents such as TMZ on MGMT promoter methylated cells ( 35 ). Moreover, our study found no significant prognostic impact from other tumor biomarkers, such as IDH and TERT promoter mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MGMT-methylated tumors had superior prognoses, potentially attributable to increased temozolomide (TMZ) sensitivity in these tumors ( 34 ). Notably, recent research on human GBM cell lines indicated a synergistic effect of combining TTFields with chemotherapy agents such as TMZ on MGMT promoter methylated cells ( 35 ). Moreover, our study found no significant prognostic impact from other tumor biomarkers, such as IDH and TERT promoter mutations.…”
Section: Discussionmentioning
confidence: 99%
“…TTFields therapy has been authorized for the treatment of newly diagnosed GBM in conjunction with maintenance temozolomide. Recent evidence has shown the efficacy of TMZ when combined with lomustine (CCNU) in patients with O6-methylguanine DNA methyltransferase (MGMT) promoter methylation, findings which reinforce the clinical advantage of using TTFields in combination with both temozolomide and lomustine [ 308 ].…”
Section: The Tumor Microenvironment In Gliomas: a Focal Pointmentioning
confidence: 97%
“…BRCA1 and BRCA2 play an important role in maintaining the fidelity of DNA replication by mediating homologous recombination repair, and downregulation of BRCA gene expression can inhibit DNA double-strand repair. 20 PARP is a protein involved in DNA repair. PARP inhibitor treatment induces cancer cell death in patients with BRCA mutations or defects.…”
Section: Ttfields Inhibit Dna Damage Repairmentioning
confidence: 99%
“…23 The combination of TTFields with sorafenib, TMZ + lomustine, RT, or hyperthermia enhances the apoptosis induced by TTFields. 15,20,24,25…”
Section: Ttfields Induce Apoptosis Of Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation